Almaciga resin purification plant a plant design - Elloso, Jeremiah L.; Esquillo, Gerald R.; Ramos, Norman L.; Vergara, Jason P. (College of Engineering, 1999)
Product: Purified almaciga resin & its essential oil -- Plant location: Nasugbu, Batangas -- Total land area: 500 sq. meters -- Annual volume of production (1st year): Resin - 179,485.5 kg, Essential oil - 11,798.7 kg -- Annual gross sales: Php18,413,251.25 -- Annual income: Php333,129.23 -- Total investment cost: Php9,932,069.69 -- Working capital: Php993,206.97 -- Product selling price: Resin - Php50, Essential oil - USD20/ml -- Product cost: Php65/kg -- ROI: 3.34% -- Payback period: 1.86 years